Caracterización morfométrica y molecular de especies de anfibios y reptiles en zonas urbanas y periurbanas de la ciudad de Iquitos - Guillen Huaman, Jorge Luis (2023)
The present study aimed at the morphometric and molecular characterization of amphibian and reptile species in urban and periurban areas of the city of Iquitos. The samples were collected in two urban and two periurban areas of the city of Iquitos and the morphometric characterization was performed by principal component analysis (PCA), while the molecular characterization was developed by nucleotide sequencing of the mitochondrial gene Cytochrome Oxidase subunit I (COI). The specific diversity of the herpetofauna in periurban areas was higher than in urban areas, finding a difference of 33 species between the two areas analyzed (peri-urban areas 45, urban areas = 12). Adenomera hylaedactyla, Boana punctata, Dendropsophus triangulum, Dendropsophus leali, Scinax ruber and Rinella marina, were present in both urban and periurban areas, and the results of the morphometric analysis allowed differentiating four of the six species analyzed: Boana punctata, Dendropsophus haraldschultzi, Dendropsophus leali, and Dendropsophus triangulum, showing to be a useful technique to differentiate species, despite this, the PCA was not effective for Adenomera andreae and Adenomera hylaedactyla. However, in the molecular characterization (Barcoding), genetic distance and mutations were observed between both species, showing that Adenomera andreae and Adenomera hylaedactyla are valid taxonomic entities. In conclusion, the present study shows the potential of using Barcoding in taxonomic studies or in herpetofaunal biodiversity inventories.